Nocardia pulmonis sp. nov., an actinomycete isolated from a patient with pulmonary infection. Issue 4 (6th April 2023) - Li, Fang; Xu, Shuai; Li, Zhenpeng; Yue, Yuan; Song, Jingdong; Du, Baozhong; Che, Yanlin; Han, Lichao; Qiu, Xiaotong; Kang, Yutong; Liu, Xueping; Chen, Shenglin; et al.
Abstract : A novel bacterial strain, CDC141 T, was isolated from sputum samples of a patient with pulmonary infection in Hainan Province, PR China. We performed a polyphasic study to assess the taxonomic position of the new species. Based on the results of 16S rRNA gene sequence analyses, strain CDC141 T belonged to the genus Nocardia with the highest sequence similarity to Nocardia nova NBRC 15556 T (98.84 %) and Nocardia macrotermiti s RB20 T (98.54 %). The dapb1 gene sequence-based phylogenetic and phylogenomic trees further showed that the novel strain was clustered in a distinct clade adjacent to Nocardia pseudobrasiliensis DSM 44290 T . The DNA G+C content of strain CDC141 T was 68.57 mol%. The genomic diversity analysis revealed low average nucleotide identity and in silico DNA‒DNA hybridization values (<84.7 and <28.9 %, respectively) with its closest relative. Growth occurred at 20–40 °C, pH 6.0–9.0 and with NaCl concentrations of 0.5–2.5 % (w/v). The main fatty acids of strain CDC141 T were C16 : 0, C18 : 0 10-methyl, TBSA, C16 : 1  ω 6 c /C16 : 1  ω 7 c, C18 : 1  ω 9 c, C18 : 0, C17 : 1 iso I/anteiso B and C17 : 0 . The polar lipid profile was dominated by diphosphatidylglycerol, phosphatidylethanolamine, phosphatidylinositol, phosphatidylinositol mannoside, unidentified glycolipids, unidentified phospholipids and unidentified lipids. MK8 (H4 ω -cycl ) and MK8 (H4 ) were the major respiratory quinones. These characteristics were consistent with the typical chemotaxonomic properties of members of the genus Nocardia . Based on the results of phenotypic and genetic analyses, strain CDC141 T was identified as representing a new species of the genus Nocardia, with the proposed name Nocardia pulmonis sp. nov. (CDC141 T =JCM 34955 T =GDMCC 4.207 T ).